Reação de bis-inserção de 1,2-difenilacetileno na ligação Pd-C de ciclometalados - Ananias, Sandra Regina [UNESP]; Santana, Anderson Martinez [UNESP]; Mauro, Antonio Eduardo [UNESP]; Lucca Neto, Vicente Alexandre de; Almeida, Eduardo Tonon de (Sociedade Brasileira de Química, 2003)
The present paper deals with the bis-insertion reactions of 1,2-diphenylacetylene into Pd-C bond of the cyclopalladated complexes [Pd(dmba)(µ-NCO)]2 (1) and [Pd(dmba)(MeCN)2](NO3) (2) (dmba = N,N-dimethylbenzylamine, MeCN = acetonitrile). Two new complexes [Pd{PhC=CPh-CPh=CPhC6H4CH2N(CH 3)2}(NCO)] (3) and [Pd{PhC=CPh-CPh=CPhC6H4CH2N(CH 3)2}(NO3 )] (4) were obtained and characterized by IR and NMR spectroscopy and elemental analysis.
Bis insertion reaction of 1,2-diphenylacetilene into Pd-C bond of cyclometallated species
Keywords: 1,2-diphenylacetylene; cyclopalladated; bis-insertion